St Thomas Cathedral - Ghosh, Ayan (2023)
The church in the name Churchgate refers to the 300-year-old St Thomas’ Church (now Cathedral). The ‘gate’ comes from the time when Bombay was protected by a Fort. The walled city had three gates, and the western gate was located close to the St. Thomas Church, hence Churchgate. Later when the railways were built, the name Churchgate was applied to the nearby railway station, as did the surrounding neighborhood.